Urban Ecological Restoration: Setting Priorities for Restoring Native Vegetation in Lava Field Remnants in Mexico City - Bonilla-Rodríguez, Manuel; Arroyo-Lambaer, Denise; Castillo, Alicia; Zambrano, Luis; Cano-Santana, Zenón (Frontiers in Sustainable Cities, 2021)
As cities overgrow, the need for ecological restoration is becoming increasingly urgent, especially in densely populated areas. Urban ecological restoration represents the best approach to undertake damages to restore native ecosystem remnants fulfilling biodiversity but also social goals in dense urban settings such as Mexico City. The feasibility of restoring unique xerophytic scrub vegetation in lava field remnants was evaluated in a portion of a university campus in Mexico City. Here we present an index (Need and Feasibility of Restoration Index, NFRI) for such purpose. The NFRI was designed through multicriteria analysis and considered ecological, economic, and social indicators. Cluster and principal components analysis were carried out to identify different groups of lava field remnants with similar characteristics and to point out critical variables that in turn would support management strategies. The outcomes made evident the necessity of restoring native vegetation for all of the evaluated remnants; however, the group containing the largest ones obtained the highest values for restoration feasibility and NFRI. The recovery of the rest of the remnants is critical to support the ecological restoration of the area as this may provide connectivity with better-preserved ecosystem remnants. When the restoration is unaffordable due to financial constraints, it is highly recommended to direct efforts towards ecological rehabilitation actions. The establishment of native xerophytic gardens is promoted when remnants cannot support a self-sustainable plant community. It is crucial to include the diversity of views and values of the community and the economic and ecological aspects to guarantee the sustainability of the landscape, especially in the urban context. The latter can provide better planning and design processes, ensuring benefits for humans and nature.